Analisis Tahapan Perkembangan Anak dalam Mengoptimalkan Potensi Diri Pada Usia 2-6 Tahun - Mustikaati, Wina; Okthaviani, Anggita; Insari, Indah Putri; Syifa, Miana; Nuralmira, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Early childhood development, particularly in the age range of 26 years, is a crucial period for shaping the foundational abilities and potential of children. The method used in this study is a qualitative approach through library research or literature review. This study examines various research findings related to the issues being investigated. During this stage, children undergo rapid growth across various developmental domains, including physical, cognitive, social-emotional, and language development. Physical development involves improvements in motor skills and overall health. Cognitively, according to Piaget, children enter the sensorimotor and preoperational stages, characterized by the use of symbols and language, although their thinking remains egocentric and concrete. Social-emotional development encompasses the ability to manage emotions, build social relationships, and interact with the surrounding environment. Meanwhile, language development is significantly influenced by stimulation from close environments such as family, school, and community. The family and school environments play a central role in providing positive stimulation essential for supporting the childs overall growth and development. Therefore, synergy between various developmental aspects and environmental support is key to optimizing holistic early childhood development.